ISOLATION, CHARACTERIZATION AND EVALUATION OF ANTIOXIDANT ACTIVITY OF SILICA CELLULOSE NANOCOMPOSITE (SiO2-CNC) EXTRACTED FROM BIO-WASTE (RICE HUSK) INTEGRATED WITH CALLISTEMON CITRINUS EXTRACT (FUDMA JOURNAL OF SCIENCES, 2025)
Recent research has focused on more complex uses, such as the extraction of silica cellulose nanocomposite from rice husks, which has potential as a way to create high-tech materials. The work describes the successful isolation, characterization, and assessment of rice husk-derived silica cellulose nanocomposite (SiO2-CNC) with Callistemon citrinus extract integration. The synthesis process consisted of three principal operations: delignification with alkaline treatment, sodium hypochlorite bleaching, and concentrated sulphuric acid hydrolysis. The prepared nanocomposite was analyzed by EDX, SEM, TEM, FTIR, spectrophotometry, and thermal analysis (DTA/TGA). EDX studies showed a composite material with elemental silica (40.20%), carbon (20.76%), silver (10.57%), and zinc (8.50%) in significant proportions. The sophisticated material structure with uniform porous networks was demonstrated by SEM analysis, while the presence of nanoparticles sized from 2.70 to 6.37 nm was confirmed by TEM. Thermal analysis showed distinct decomposition steps beyond 250oC, and material stability was observed up to these temperatures. FTIR spectroscopy verified the functional groups in SiO2-CNC and the rice husk extract, while UV analysis showed strong absorption in the 200-230 nm range. Callistemon citrinus extract showed the ability to enhance the antioxidant properties of SiO2-CNC, which was observable in DPPH and ABTS assays. The integrated composite showed significant DPPH and ABTS radical scavenging activities. These findings demonstrate the successful conversion of agricultural waste into a value-added nanocomposite with enhanced functional properties, offering potential application in antioxidant delivery systems, and advanced materials development. This research contributes to sustainable nanomaterial development while addressing agricultural waste management challenges.
Keywords: Rice-husks; Silica cellulose nanocomposite (SiO2-CNC); EDX; SEM; TEM; FTIR